Health Technology Assessment (HTA) Institutionalisation in the UAE: The Complex Interactions Between Health Policy Context, Actors, and Content in a Health Policy Reform - AHMAD, MAISS (2022)
Innovative technologies are credited with significant improvements in health indicators, but they come at a high financial impact. Health Technology Assessment (HTA) is a universally established tool to rationally assess the value of health innovations. Despite its acknowledged value, almost one-third of countries have not institutionalised HTA in their systems yet. The United Arab Emirates (UAE) is a pioneering country in adopting health innovations, this emphasises the importance of exploring when and how the UAE will establish the HTA in its health system to guide the decision-making process of adopting innovative health technologies. This study aims to provide an in-depth health policy analysis of an ongoing, and prospective HTA institutionalisation process. This case study used a hybrid framework combining the Walt-Gilson triangle, the Dunlop and Raedelli framework, stakeholder analysis, and policy participation rules. Data were collected from document reviews and semi-structured interviews and analysed by the codebook thematic analysis. The findings outline multiple interlinked facilitators and challenges in the predicted HTA establishment process. While certain elements were found to be associated with certain phases in the envisioned process, policy learning and policy participation rules were found to be associated with all the phases of the process, and, therefore, require the most political and scientific attention. The originality of this research lies in designing and testing a new hybrid framework to examine health policy reforms. The findings are projected to support global organisations, academics, and HTA policy entrepreneurs in designing more effective HTA policy learning programmes.